Future Economy and Touristic Entrepreneurship - Jelev, Viorica (Journal of Economic Development, Environment and People, 2016)
Specialists claim that Eco-Bio-economy or social economy is the economy of future, in the service of human life by the rational use of environmental resources. The concept brings together in an integrated manner, according to the researchers, economy, ecology, biodiversity, biotechnologies and focuses on integrated sustainable development of the world. The new social economy, together with the corporate social responsibility joins a new multipolar world to a healthy environment by creative and innovative concepts that will ensure the sustainability of living in a sustainable manner. Doctors have added to thisEco-Bio-Economy concept a new one called One Health - a new integrated approach for human, animals and environment health state to that they should emphasize the importance of human behavior upon the planet biodiversity. Economer agents have mostly understood the importance of alarm signals drawn up by researchers on the destruction of the resources of the planet and adapted their business sites to the requirements of the green economy. A responsible business is also ecotourism that promotes a favourable travel for the surrounding environment. It requires accommodation on farms, in peasant houses, small rural hotels. The educational environment contributes to the trend planetary tourism, with the formation of new specialists with new knowledge, behaviors and consumers use formation of new characters, sensitive to environmental issues. This educational model is also promoted by Spiru Haret University, by creating the Master degree in tourism but also in environmental protection.